2013
DOI: 10.1038/srep01103
|View full text |Cite
|
Sign up to set email alerts
|

Feedback Mechanism in Depolarization-Induced Sustained Activation of Extracellular Signal-Regulated Kinase in the Hippocampus

Abstract: Phosphorylation plays important roles in several processes including synaptic plasticity and memory. The critical role of extracellular signal-regulated kinase (ERK) in these processes is well established. ERK is activated in a sustained manner by different stimuli. However, the mechanisms of sustained ERK activation are not completely understood. Here we show that KCl depolarization-induced sustained ERK activation in the hippocampal slices is critically dependent on protein synthesis and transcription. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 58 publications
(78 reference statements)
1
18
0
Order By: Relevance
“…With regards to ERK, it has been demonstrated to promote CM survival, and could be activated by the GPCR, Ras/Raf cascade [50]. Indeed, potassium-induced depolarization activated ERK and proline-rich tyrosine kinase in the central nervous system [51, 52] and a similar result was also found in CMs treated with potassium channel blockers [53]. In our study, ERK 1/2 was fairly consistent across both treatment groups; however activated ERK (pERK1/2) is upregulated in both potassium and ouabain groups.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to ERK, it has been demonstrated to promote CM survival, and could be activated by the GPCR, Ras/Raf cascade [50]. Indeed, potassium-induced depolarization activated ERK and proline-rich tyrosine kinase in the central nervous system [51, 52] and a similar result was also found in CMs treated with potassium channel blockers [53]. In our study, ERK 1/2 was fairly consistent across both treatment groups; however activated ERK (pERK1/2) is upregulated in both potassium and ouabain groups.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that ERK activity is indeed regulated by different stimuli, among which we chose three examples. (1) KCl depolarization induces sustained ERK activation in hippocampal neurons (27, 28). (2) Selective extrasynaptic NMDA receptor activation (as well as NMDA bath application) does not activate ERK pathways, whereas (3) synaptic NMDAR activation – to induce a chemical LTP – induces ERK activation (29).…”
Section: Resultsmentioning
confidence: 99%
“…Male rats that were 6-8 weeks old were used for the experiments. For immediate ERK activation analysis, the slices were incubated for 1.5 h with the inhibitor (emetine, 20 mM [15], or actinomycin D, 25 mM [15]) during the recovery period and then treated with forskolin + Ro-20-1724 for 15 min, after which they were rinsed with aCSF and harvested in the lysis buffer. The animals were anaesthetized with halothane (Sigma-Aldrich, St. Louis, Missouri, USA) before killing.…”
Section: Preparation Of Hippocampal Slices and Treatmentmentioning
confidence: 99%
“…After treatments, the slices were washed with aCSF and the entire slice [15,16] was lysed in SDS containing lysis buffer (50 mM Tris-Cl, pH 7.5, 150 mM NaCl, 1 mM EDTA, 1 mM EGTA, 50 mM sodium fluoride, 1 mM sodium orthovanadate, 1 mM sodium butyrate, 2% SDS, and a protease inhibitor cocktail). After lysis, the samples were boiled for 5 min and clear supernatant containing solubilized proteins was collected after centrifugation.…”
Section: Sample Preparation and Immunoblottingmentioning
confidence: 99%
See 1 more Smart Citation